1996
DOI: 10.1007/bf02284689
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective, follow-up study of biofeedback-assisted relaxation therapy in patients with posttraumatic headache

Abstract: Although biofeedback in the treatment of migraine and tension-type headache has been widely researched, there is little research examining biofeedback therapy in posttraumatic headache (PTH). In this retrospective study, 40 subjects with PTH who had received biofeedback-assisted relaxation at our headache clinic were questioned at least 3 months following the completion of therapy. Subjects were queried about improvements in headache, increases in ability to relax and cope with pain, and overall benefits, last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…We identified ten articles that specifically addressed the treatment of headache after TBI. [17][18][19][20][21][22][23][24][25][26] Among these ten studies, two were single case reports, three were case series, and the remaining five were either retrospective or prospective studies without controls. Details regarding the type and the design of these studies are described in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified ten articles that specifically addressed the treatment of headache after TBI. [17][18][19][20][21][22][23][24][25][26] Among these ten studies, two were single case reports, three were case series, and the remaining five were either retrospective or prospective studies without controls. Details regarding the type and the design of these studies are described in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…20 Two uncontrolled studies investigated the effectiveness of relaxation and biofeedback in PTH. 22,23 They both showed favorable results. In a prospective, nonrandomized, uncontrolled study, a combined therapy of medication, relaxation, and biofeedback showed the most dramatic improvement.…”
Section: Treatment For Posttraumatic Headachementioning
confidence: 90%
“…A similar finding of QEEG normalization following EEG biofeedback was reported by Byers (1995), tinius and tinius (2001), Bounias et al (2001Bounias et al ( , 2002, Wing (2001), Laibow et al (2001), and Schoenberger et al (2001). Ham and packard (1996) evaluated EEG biofeedback in 40 patients with post-traumatic head ache. they reported that 53% showed at least moderate improvement in headaches, 80% reported moderate improvement in ability to relax and cope with pain, and 93% found biofeedback helpful to some degree.…”
Section: Qeeg Biofeedbackmentioning
confidence: 99%
“…In general, chronicity of posttraumatic pain predicts a poorer response for improvement in therapeutic paradigms dominated by BF. 30 Another challenging population of headache patients is the group who use high doses of multiple classes of medication. Withdrawal of medication, which can be accomplished, although with diffi culty, on an outpatient basis, should precede treatment in this group.…”
Section: Headachementioning
confidence: 99%